Multidrug-resistant (MDR) Klebsiella pneumoniae clinical isolates: a zone of high heterogeneity (HHZ) as a tool for epidemiological studies - Ramirez, Maria Soledad (2012)
Comparison of genome-wide, high-resolution restriction maps of Klebsiella pneumoniae clinical isolates, including an NDM-1 producer, and in silico-generated restriction maps of sequenced genomes revealed a highly heterogeneous region we designated the ‘high heterogeneity zone’ (HHZ). The HHZ consists of several regions, including a ‘hot spot’ prone to insertions and other rearrangements. The HHZ is a characteristic genomic area that can be used in the identification and tracking of outbreak-causing strains.